Educational philosophy in Islam in the curriculum design of integrated Islamic education in Malaysia - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (Postgraduate of State Institut for Islamic Studies Pekalongan, IAIN, 2019)
This article discusses the dichotomy in Islamic education which is the basic problem facing Islamic education today. To overcome these problems, one of them is by organizing an educational model that integrates the science of religion with the knowledge that is based on the philosophy of Islamic education. By employing qualitative method of research, this article strives to identify the philosophy of education in Islam and challenges in the current integrated educational system, which is currently implemented in Malaysian primary and secondary schools. The results of this study, concluded that in overcoming the problem in the preaching of Islamic education, Malaysia implemented integrative Islamic education that integrates religion and science with the Ulul al-Bab model and the KAFFAH curriculum. The concept of Ulul al-Bab is taken from the Qur'an as the basis of the curriculum, while in the KAFFAH curriculum each subject taught is associated with Islamic values and beliefs. ************************************************************************************ Artikel ini membahas dikotomi dalam pendidikan Islam yang merupakan masalah mendasar yang dihadapi pendidikan Islam saat ini. Untuk mengatasi masalah tersebut, salah satunya adalah dengan menyelenggarakan model pendidikan yang mengintegrasikan ilmu agama dengan ilmu pengetahuan yang landasi oleh filosofi pendidikan Islam. Dengan menggunakan metode penelitian kualitatif, artikel ini berupaya mengidentifikasi filosofi pendidikan dalam Islam dan tantangan dalam sistem pendidikan terintegrasi yang saat ini diterapkan di sekolah dasar dan menengah di Malaysia. Hasil penelitian ini, diperoleh kesimpulan bahwa dalam mengatasi masalah dikhotomi pendidikan Islam, Malaysia menerapkan pendidikan Islam integratif yang mengintegrasikan antara agama dan ilmu pengetahuan dengan model Ulul al-Bab dan kurikulum KAFFAH. Konsep Ulul al-Bab diambil dari Al-Qur'an sebagai dasar kurikulum, sedangkan dalam kurikulum KAFFAH setiap mata pelajaran yang diajarkan dikaitkan dengan nilai-nilai dan keyakinan Islam.